THE ROLE OF STAKEHOLDERS IN THE IMPLEMENTATION OF PAYMENT FORWATER ENVIRONMENTAL SERVICES IN THE BANTIMURUNG BULUSARAUNG NATIONAL PARK, PANGKEP REGENCY, SOUTH SULAWESI - Nur Hayati; Abdul Kadir Wakka (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
The potentiality of water resources owned by Bantimurung Bulusaraung National Park (Babul NP) is abundant and has been utilized by the community around the area. The concept of payment for environmental services is very possible to be applied to Babul NP in an effort to preserve water resources. Therefore, stakeholders in the utilization of water environmental services in Babul National Park need to be identified. This study aims to map the stakeholders in the utilization of water environmental services in the Babul NP area, as well as the parties who need to be involved if the concept of payment for environmental services to be applied to the management of water environmental services in Babul NP. Data collection was carried out through direct observation, in-depth interviews, questionnaires filling by key informants, and focused group discussions. Data were analyzed by using stakeholders analysis. The results showed that stakeholders who could be directly involved in the utilization of water environmental services related to the payment for environmental services are among others the community around the area, industry, the Regional Water Company (PDAM), Babul NP, and the villages. The selection of the proper stakeholders will greatly affect the successful implementation of the payment for water environmental services concept in Babul NP